Japanese Herbal Kampo Hochu-Ekki-To or Juzen-Taiho-To after Surgery for Hip Fracture Does Not Reduce Infectious Complications - Yusuke Sasabuchi (Evidence-Based Complementary and Alternative Medicine, 2018)
Background. Infectious complications after hip fracture surgery are common in the elderly. Although experimental studies have suggested that kampo medicine, Hochu-ekki-to and Juzen-taiho-to, can prevent infectious complications, only a few small clinical studies have been published to date. Primary Study Objective. The aim of the present study is to investigate the impact of Hochu-ekki-to or Juzen-taiho-to on postoperative infectious complications in patients undergoing surgery for hip fracture. Methods and Design. In this retrospective cohort study using a nationwide inpatient database in Japan, we performed propensity score matching to compare patients who did or did not receive kampo medicine after surgery for hip fracture. Settings. A nationwide inpatient database. Participants. Patients who did or did not receive kampo medicine after surgery for hip fracture. Intervention. Kampo medicine after surgery for hip fracture. Primary Outcome Measures. Infectious complications. Results. The proportions of postoperative infectious complications were not significantly different between the 424 propensity-matched pairs with and without kampo medicine (11 versus 8, P=0.644). Conclusion. The present study suggests that Hochu-ekki-to or Juzen-taiho-to postoperatively is not associated with decreased occurrence of infectious complications in patients who underwent surgery for hip fracture.